Temporal Coupling of Eye Gaze and Cursor on Key Buttons during Text-Entry Tasks. Issue 1 (February 2014) - Hong, Seung-Kweon; Myung, Rohae
Coupling patterns of eye gaze and cursor movements on key buttons were investigated during a practical text-entry task. A text-entry task can be described as a series of goal-directed aiming tasks. In a typical goal-directed aiming task, eye movements generally lead cursor movements; eye gaze arrives at the target and starts moving to the next target before the cursor. However, in 10% of cases in this experiment, the cursor arrived at the target earlier than the eye gaze did, regardless of text entry speed. Eye gaze started toward the next target key button after the start of the cursor's movement in 57% of cases, which also varied with text-entry speed. The coupling patterns, which differed from those observed in typical goal-directed aiming tasks, might be due to the speed requirement of practical text-entry tasks, memory of key button positions, and the use of peripheral vision.